Bartech - Aplicación web que sirve como herramienta para gestión de música en los bares de la ciudad de Bogotá D.C (2024)
The objective of this degree work was to develop a web application called Bartech. The application was created to allow better management of housekeeper clients in bars. The web application would not only improve the customer experience but would also make the staff's work easier and more efficient. This application was developed using modern technologies in a user-friendly interface combined with a robust architecture that supports scalability and data security. Bartech's mission is to provide a platform that improves customer and staff interaction using a technological solution that adapts to modern digitalization trends and digital transformation.